Systems Approach to an Optimal Organization (American Journal of Development Studies, 2023)
Antoinette Ryan’s “A Systems Approach to Career Education” exemplifies systems approach to an organizational success. This paper provides a theoretical review on the principles of wholeness, systematization, compatibility, and optimization as elements in an organizational process. The paper reveals that optimization is an undertaking that entails both management and members of an organization to work as a team with the conscious effort of bringing the organization to its desired plan. Optimization is not only realized when big plans are achieved but specific targets need to be met as well.